Calculating Sustainable Non-mineral Balances as Benchmarks for Fiscal Policy : The Case of Botswana - Clausen, Jens (IMF Working Papers; Working Paper ;, 2008)
Assuming a social welfare function that smoothes expenditure, this paper calculates a sustainability benchmark for the non-mineral balance in Botswana that is based on a notion of a "permanent income" from non-renewable resources. It is derived by constructing a hypothetical annuity from revenues from these resources, which is held constant in terms of GDP. Botswana is an interesting case because current projections suggest that diamond resources could be largely exhausted within a generation.